Everyday Life. First Steps for a Philosophical Conceptualization [Cotidianidad. Trazos Para Una Conceptualización Filosófica] - Santos-Herceg, J (Universidad de los Lagos, 2014)
This study aims to overcome some authors feeling that -everyday life{norm of matrix} is a vague, problematic and polysemous concept which, for those reasons, is unreachable and even imperceptible. This task is more relevant at present, considering the central importance that -everyday life{norm of matrix} category has gained in contemporary studies. We have approached this task starting from the analysis of different problems: first, the question of the universality of this concept; second, its narrative nature, its heterogeneity and necessary homogeneity (regulations); third, the possible motivations; fourth, its interruption or break down; then, its difference and proximity to the concept of -routine{norm of matrix} and; finally, its consequences: dis-enchantment and boredom.